Downtown revitalization: planning for St. Joseph’s future - Graham, Jeffery (Kansas State University, 2011)
Historically downtown St. Joseph was a vibrant urban center where many people came for entertainment and shopping (Bunkowski, 2010). With the rise of the automobile in the 1950’s and 60’s, the city has become largely focused around auto-oriented development. The downtown has been separated from the Missouri River with the construction of Interstate 229 and rail lines, limiting access to the riverfront. Overtime, some of the sites have become contaminated and are now designated as brownfields. Redevelopment of downtown St. Joseph can help solve these problems, and help position the city for future development. By restructuring existing buildings and planning for future infill, as well as incorporating green space into the design of the area, the downtown can once again be a vibrant, vital area of the city. The redevelopment of downtown St. Joseph will focus around creating walkable mixed-use urban fabric that attracts people to the city’s core. Downtown St. Joseph will once again become an important economic and social center for the city. New mixed use development in the downtown will provide places for new businesses and residences in the city. Enhanced connections to the surrounding areas will increase access to the downtown and parks in the area. Improvements to the downtown will make the area a vital part of St. Joseph.
Keywords: Downtown revitalization; Landscape Architecture (0390)